2020
DOI: 10.3390/plants9040438
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of Peltophorum dubium (Spreng.) Taub. extracts against Aspergillus flavus

Abstract: Aspergillus flavus is a filamentous, saprophytic fungus, whose colonization occurs mainly in cereal grains and oilseeds once harvested. Under certain conditions, it could produce mycotoxins called aflatoxins, known as powerful human liver carcinogens. The aim of the present study was to describe the antifungal activity of extracts of Peltophorum dubium, a species from northern Argentina (Oriental Chaco), against A. flavus. The antifungal activities of different collection sites are reported. The extracts exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The production of 2-Phenylethanol could affect gene expression and exert its biological control ability ( Hua et al, 2014 ; Loi et al, 2020 ) And inhibit spore germination and aflatoxin formation in A. flavus . and decrease gene expression of clustering aflatoxin biosynthesis genes as evidenced ( Di Ciaccio et al, 2020 ). In the report that 2-Phenylethanol exhibited strong antibacterial activity by breaking the bacterial cell membrane ( Monggoot et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…The production of 2-Phenylethanol could affect gene expression and exert its biological control ability ( Hua et al, 2014 ; Loi et al, 2020 ) And inhibit spore germination and aflatoxin formation in A. flavus . and decrease gene expression of clustering aflatoxin biosynthesis genes as evidenced ( Di Ciaccio et al, 2020 ). In the report that 2-Phenylethanol exhibited strong antibacterial activity by breaking the bacterial cell membrane ( Monggoot et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…The authors concluded that P. dubium extracts altered the fungal cell wall and membrane. The presence of flavonoids, including kaempferol, naringenin, chrysin, daidzein and apigenin, was detected in the active extracts [ 5 ].…”
Section: Using Various Methodologies To Discover New Plant-derivedmentioning
confidence: 99%
“…Fungal cell membrane damage was observed by Evans blue staining according to the method of Lucía S. Di Ciaccio et al [36]. An amount of 100 µL of mycelial suspension at 1 mg/mL concentration was added to a conical flask containing 25 mL of PDB and incubated in a shaker at 28 • C ± 2 • C and 200 rpm for 12 h. Various volumes of the stock solution of 25 mg/mL natamycin emulsion were pipetted into the conical flask to achieve final concentrations of 6.25, 12.5, and 25 µg/mL, corresponding to 1/16, 1/8, and 1 4 MIC, respectively.…”
Section: Effect Of Natamycin On the Cell Membrane Of N Parvummentioning
confidence: 99%